2002
DOI: 10.1101/gad.228802
|View full text |Cite
|
Sign up to set email alerts
|

In the complex family of heat stress transcription factors, HsfA1 has a unique role as master regulator of thermotolerance in tomato

Abstract: We generated transgenic tomato plants with altered expression of heat stress transcription factor HsfA1. Plants with 10-fold overexpression of HsfA1 (OE plants) were characterized by a single HsfA1 transgene cassette, whereas plants harboring a tandem inverted repeat of the cassette showed cosuppression (CS plants) by posttranscriptional silencing of the HsfA1 gene connected with formation of small interfering RNAs. Under normal growth conditions, major developmental parameters were similar for wild-type (WT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
481
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 509 publications
(524 citation statements)
references
References 57 publications
21
481
3
1
Order By: Relevance
“…2D). Hsp101 protein has been also previously shown to accumulate in leaves of A1CS plants, suggesting efficient translation and Hsp101 protein accumulation even at reduced transcript levels (Mishra et al, 2002). The reduced accumulation of Hsps in heat-stressed leaves of A2AS lines compared to the wild type indicates that HsfA2 plays an important role as coactivator during induction of the HSR.…”
Section: The Role Of Hsfa2 In Heat Stress Response Of Young Leaves Anmentioning
confidence: 89%
See 2 more Smart Citations
“…2D). Hsp101 protein has been also previously shown to accumulate in leaves of A1CS plants, suggesting efficient translation and Hsp101 protein accumulation even at reduced transcript levels (Mishra et al, 2002). The reduced accumulation of Hsps in heat-stressed leaves of A2AS lines compared to the wild type indicates that HsfA2 plays an important role as coactivator during induction of the HSR.…”
Section: The Role Of Hsfa2 In Heat Stress Response Of Young Leaves Anmentioning
confidence: 89%
“…We generated transgenic plants expressing a cDNA cassette of tomato HsfA2 either in the sense (A2S) or in antisense orientation (A2AS) under the control of the Cauliflower mosaic virus (CaMV) 35S promoter as previously described for HsfA1a (Mishra et al, 2002). We selected three independent transgenic lines (A2AS-3, -7, and -15) with significantly reduced HsfA2 levels as confirmed by transcript analysis using qRT-PCR in seedlings (Fig.…”
Section: The Role Of Hsfa2 In Heat Stress Response Of Tomato Seedlingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, 21 Hsfs have been identified (Nover et al, 2001). Interestingly, it seems that in Arabidopsis, different from tomato (Solanum lycopersicum; Mishra et al, 2002), there is not a unique master regulator for the Hsf-mediated heat shock response. Different Hsfs have been identified as potential crucial element for Arabidopsis response not only to heat stress (Busch et al, 2005;Schramm et al, 2006Schramm et al, , 2008Charng et al, 2007) but also to oxidative stress (Li et al, 2005;Nishizawa et al, 2008), hydrogen peroxide (H 2 O 2 ), high light (Nishizawa et al, 2006), and salt stress as well (Ogawa et al, 2007).…”
mentioning
confidence: 99%
“…In another independent study, hsf3 gene over-expressed in A. thaliana resulted in increased thermotolerance (Panchuk et al, 2002). Mishra et al (2002) over-expressed tomato hsfA1 gene in tomato plants. In this study, overexpressing lines showed increased thermotolerance while transgenic lines in which transgene was silenced due to cosuppression were thermosensitive.…”
Section: High Temperature Tolerant Transgenics Raised Through Alterinmentioning
confidence: 94%